Rev Proteins of Human and Simian Immunodeficiency Virus Enhance RNA Encapsidation - Brandt, Sabine (Public Library of Science, 2007)
The main function attributed to the Rev proteins of immunodeficiency viruses is the shuttling of viral RNAs containing the Rev responsive element (RRE) via the CRM-1 export pathway from the nucleus to the cytoplasm. This restricts expression of structural proteins to the late phase of the lentiviral replication cycle. Using Rev-independent gag-pol expression plasmids of HIV-1 and simian immunodeficiency virus and lentiviral vector constructs, we have observed that HIV-1 and simian immunodeficiency virus Rev enhanced RNA encapsidation 20- to 70-fold, correlating well with the effect of Rev on vector titers. In contrast, cytoplasmic vector RNA levels were only marginally affected by Rev. Binding of Rev to the RRE or to a heterologous RNA element was required for Rev-mediated enhancement of RNA encapsidation. In addition to specific interactions of nucleocapsid with the packaging signal at the 5′ end of the genome, the Rev/RRE system provides a second mechanism contributing to preferential encapsidation of genomic lentiviral RNA.